Corporate Culture and Organizational Performance : The Mediating Role of Psychological Well-Being - Mishra, Paritosh; Yadav, Anshu; Awasthi, Shweta; Kaur, Jaideep; Johar, Seema (Prabandhan: Indian Journal of Management, 2026)
Purpose : Prior research has frequently attributed superior performance to an enabling organizational culture. But what remained unexplored was the answer to the question of “how?” Further, psychological well-being at work, albeit an important variable, received scant attention from researchers regarding its role in shaping the association between organizational performance and corporate culture. Therefore, this study examined the relationship between corporate culture and organizational performance and investigated the mediating role of psychological well-being in this relationship. Design/Methodology : The research was carried out using a descriptive, quantitative research design. A survey questionnaire was administered, convenience sampling was used to select participants, and data were analyzed using partial least squares structural equation modeling. Findings : The proposed model indicated that psychological well-being at the workplace mediated the association between corporate culture and firm performance. Practical Implications : This study has significant managerial implications, especially during periods of volatility, uncertainty, complexity, and ambiguity. The study suggested that managers could achieve higher organizational performance by originating and executing new, innovative measures aimed at keeping employees happy. Originality/Value : This research added value to the extant literature by integrating corporate culture, psychological well-being, and organizational performance within a single mediation framework. The integration of micro-employee variables with macro-organizational outcomes advanced theoretical development and offered practical implications.